Assessing Large Multimodal Models for Urban Floodwater Depth Estimation - Heng Lyu; Shun'an Zhou; Ze Wang; Guangtao Fu; Chi Zhang (Water Resources Research)
Abstract Urban flood monitoring is crucial for understanding flood processes and implementing management strategies. However, current monitoring systems cannot comprehensively capture urban flooding dynamics. Here we explore the use of cutting‐edge Large Multimodal Models (LMMs) to estimate floodwater depth from ground‐level images, as alternative observational approaches. Evaluated on two urban flood image data sets, LMMs generate estimations exhibiting acceptable concordance to ground truth, with GPT‐4 achieving the highest accuracy of 0.65 and a Spearman correlation coefficient of 0.88. Furthermore, a combined effect of image complexity and textual prompt is found to influence LMMs' performance. Our study systematically demonstrates, for the first time, that LMMs can be effective tools for imaging‐based urban flood monitoring, enlarging the data for flood forecasting and model calibration.